Effect of nanosecond pulsed electric field treatment on cell proliferation of microalgae. (January 2019) - Buchmann, Leandro; Frey, Wolfgang; Gusbeth, Christian; Ravaynia, Paolo S.; Mathys, Alexander
Graphical abstract: Highlights: Innovative upstream process for photoautotrophic microalgae. nsPEF induced abiotic subcellular stress. Increased cell proliferation after nsPEF treatment. Impedance measurement of single A. platensis cells up to 10 7  Hz. Possible stress response mechanism revealed. Abstract: Photoautotrophic microalgae based biorefinery concepts are currently not competitive compared to other established production systems. Therefore, innovative upstream processes need to be developed to increase the competitiveness of photoautotrophic microalgae biorefinery concepts. Abiotic sub-lethal stress induction via nanosecond pulsed electric field (nsPEF) treatment might be a viable process to increase the efficiency of photoautotrophic microalgae cultivation. In this work, an increased cell growth after nsPEF treatment was observable. Application of nsPEF to highly proliferating cells in a repetitive process resulted in a statistical significant increase in cell growth (p = 0.009). The effect was most pronounced after five days wherefore cellular structures and processes were analyzed to reveal a possible mechanism. Within this work, a protocol for increased cell proliferation with a possible mechanism was derived, which improves competitiveness of photoautotrophic microalgae biorefineries in the future. However, based on the derived mechanism, the results are also relevant for other microorganisms.